Design and operation of a high-heat flux, flush-mounted 'rail' Langmuir probe array on Alcator C-Mod. (August 2017) - Kuang, A.Q.; Brunner, D.; LaBombard, B.; Leccacorvi, R.; Vieira, R.
Highlights: Toroidally-extended, flush-mounted 'rail' Langmuir probes survived the 2015-2016 campaign. Field-aligned, toroidally-extended probes successfully mitigated sheath expansion. Significant and systematic difference exist in plasma parameter measurements between 'rail' and standard proud probes suggesting that there are important probe-plasma interactions not currently considered. 'Death-ray' on flush mounted probes are different which may provide insight into this unique phenomenon. Abstract: A poloidal array of toroidally-extended, flush-mounted 'rail' Langmuir probes was recently installed on Alcator C-Mod's vertical target plate divertor. The aim was to investigate if a Langmuir probe array could be designed to survive reactor-level heat fluxes and have the ability to make measurements that could be reliably interpreted under reactor-level plasma densities, neutral densities and magnetic fields. Langmuir probes are typically built to have incident field-line angles > 10° to avoid interpretation issues associated with sheath expansion. However, at the high parallel heat fluxes experienced in reactor-relevant conditions such a probe would quickly overheat and melt. To mitigate both the issues of extreme heat flux and sheath expansion, each probe was designed to be flush with the divertor surface, toroidally-extended and field-aligned, giving it a 'rail' geometry. The flush mounted probes have proven to be exceptionally robust surviving the 2015–2016 campaign – a first for a C-Mod probe system. Examination of the probe current-voltage (I-V) characteristics reveals that they are immune to sheath expansion at incident field angles down to ∼0.5°. Comparison of the flush probes to traditional proud probes shows that both measure the same electron pressure across the divertor plate. However, there are significant and systematic differences in the density, temperature and floating potential. This suggests that there is important physics, perhaps unique to conditions in a vertical-target plate divertor with small field-line attack angles, that affects the I-V characteristics and is not currently included in probe data analyses. Finally, the probe response is examined in the 'death-ray' regime, just near detachment. Previous work using proud probes has suggested that the 'death-ray' is an artefact of the probe bias. However, on flush mounted probes the 'death-ray' manifests itself under different conditions, which may provide insight into this unique phenomenon.